Coaching effectiveness within competitive youth football: youth football coaches’ and athletes’ perceptions and practices - Santos, Fernando (2018)
Competitive youth sport can provide solid grounds for positive youth development (PYD). However, there is need to understand if coaches are facilitating these types of outcomes. The purpose of this study was to analyze how competitive youth sport is used to facilitate PYD. The participants in this study were four youth football coaches and 19 adolescent athletes from competitive leagues at north of Portugal. Data were collected through semi-structured interviews, field notes and nonparticipant observations. The majority of the coaches communicated appropriately and facilitated positive interactions with youth athletes. Nevertheless, the participants did not implement an explicit approach towards the development of confidence, character, connection and competence (i.e., 4 C’s) which has been linked to less PYD outcomes. Performance outcomes in certain moments superseded PYD ones. Moving forward, coaches need to comprehend how they can use their interpersonal knowledge to integrate the 4 C’s within competitive youth sport.